2018
DOI: 10.15283/ijsc18033
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Replication and Differentiation Potential of Human Bone Marrow Stem Cells by Nicotinamide Treatment

Abstract: Background and ObjectivesTherapies using mesenchymal stem cells (MSCs) generally require substantial expansion of cell populations. However, the replicative life span of MSCs is limited and their multipotency declines over continued passages, imposing a limitation on their application especially in aged individuals. In an effort to increase MSC life span, we tested the effects of nicotinamide (NAM), a precursor of NAD+ that has been shown to reduce reactive oxygen species generation and delay the onset of repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Senescent cells often exhibit a characteristic accumulation of dysfunctional autophagolysosomes, portrayed as a yellowish-green granulated cytoplasm when treated with Acridine Orange [1,30,36], as seen in the control group. Altogether, our data is consistent with the literature [11,24], as treatment with senolytics AICAR and NAM, especially AICAR, prevented most of the morphological features of senescence in our MSCs, as shown by smaller cell surface area, lower frequency of SA-β-gal-positive cells, and accumulation of autophagolysosomes in the cytoplasm.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Senescent cells often exhibit a characteristic accumulation of dysfunctional autophagolysosomes, portrayed as a yellowish-green granulated cytoplasm when treated with Acridine Orange [1,30,36], as seen in the control group. Altogether, our data is consistent with the literature [11,24], as treatment with senolytics AICAR and NAM, especially AICAR, prevented most of the morphological features of senescence in our MSCs, as shown by smaller cell surface area, lower frequency of SA-β-gal-positive cells, and accumulation of autophagolysosomes in the cytoplasm.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, García-Prat et al showed that treating old mice with a rapamycin regimen increased autophagy and re-established cell proliferation [18]. Additionally, Ok et al demonstrated that human bone marrow MSCs treated with NAM had increased autophagy [24]. According to Morselli et al, increasing autophagy is an integral part of the geroprotection, and without it, senolytics would not show any apparent protection against aging [59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect seems to occur through positive modulation of mitochondrial oxidative phosphorylation (OXPHOS) (Zhang et al, 2016), but how OXPHOS prevents stem cell senescence is yet to be determined. Moreover, NAM has recently been shown to increase lifespan of mesenchymal stem cells by delaying replicative senescence (Ok et al, 2018).…”
Section: Introductionmentioning
confidence: 99%